Searching for active ageing's intellectual sources - Szukalski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Active ageing is more and more popular concept treated as medicine against expected problems of increasing proportions of the elderly. Active ageing approach has relatively short history because it was started in 1980. In particular intellectual climate. The paper is aimed at indicating genesis of the approach due to analysis how some ways of thinking popular in the second half of the 20thcentury affected the concept. Attention is paid to phenomenology, critical gerontology, neoliberalism, processual approach and future studies.